2016
DOI: 10.1590/1983-084x/15_127
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antagonista do óleo essencial de Lippia alba (Mill.) N. E. Brown (Verbenaceae) sobre Meloidogyne incognita (Kofoid & White) Chitwood

Abstract: RESUMO: O controle de fitonematóides é uma tarefa difícil. A alta infestação de nematoides no solo obriga os produtores a usarem doses mais elevadas de nematicidas, ou ainda, a aumentarem a freqüência das aplicações, geralmente no solo, ocasionando maior potencial de dano ao homem e ao ambiente. Além disso, nematicidas convencionais vêm sofrendo grandes restrições de uso em muitos países. Desse modo, a busca de novas medidas de controle de fitonematóides é uma prioridade da agricultura sustentável. Desta forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…(Ntalli et al 2011;Silva et al 2013). Compounds such as 2,3-butanediol, sabinene, eucalyptol, limonene, and a-thujene found in sunflower seed emission were also reported in other volatilomes with activity against M. incognita (Barros et al 2014b;Gonçalves et al 2016;Silva et al 2013) but were not retained in the water.…”
Section: Discussionmentioning
confidence: 95%
“…(Ntalli et al 2011;Silva et al 2013). Compounds such as 2,3-butanediol, sabinene, eucalyptol, limonene, and a-thujene found in sunflower seed emission were also reported in other volatilomes with activity against M. incognita (Barros et al 2014b;Gonçalves et al 2016;Silva et al 2013) but were not retained in the water.…”
Section: Discussionmentioning
confidence: 95%
“…VOCs produced by sunflower (Helianthus annuus) seeds cause high mortality in M. incognita [43]. VOCs found in the plant, such as 2,3-butanediol, sabinene, eucalyptol, limonene, and α-thujene, have also been reported to be active against M. incognita in other studies [53,73,74]. The essential oil of Artemisia nilagirica has strong nematicidal activity against M. incognita [44].…”
Section: Nematicidal Vocs From Asteraceaementioning
confidence: 96%
“…This is responsible for the inhibitory activity of hatching and mortality of M. incognita juveniles. Gonçalves et al (2016) analyzed the activity of the Lippia alba (Verbenaceae) essential oil on Meloidogyne sp., they verified that this oil contains compounds with significant effects on the mortality of juveniles of second stage of M. incognita. The three L. alba essential oil chemotypes show a similar effect at the concentration of 1,000 ppm, causing mortality above 99% of M. incognita juveniles (J 2 ).…”
Section: (A) (B)mentioning
confidence: 99%
“…There are many studies that demonstrate the efficiency of essential oils such as the following: Eucalyptus camaldulensis, E. saligma and E. urophylla on mortality and hatching of Meloidogyne exigua J 2 juveniles , the essential oil of Eucaliptus sp. on J 2 M. incognita (Ibrahim et al, 2006), the effect of the essential oils of Lippia sidoides, Ocimum gratissimum, Cymbopogon winterianus, Cymbopogon citratus, Lippia alba and Eucalyptus terenticornis on the hatch of the second stage juveniles (J 2 ) of M. incognita race 2 (Moreira et al, 2009), the essential oil of Kadsura heteroclite against M. incognita (Li et al, 2011), the essential oil of L. alba in the control of M. incognita race 1 (Marino et al, 2012), the essential oil of Vigna radiata in the control of gall nematodes, Meloidogyne sp., (Wani and Bhat, 2012), Myrtus communis essential oil on the mortality of J 2 of M. incognita (Ardakani et al, 2013), the effect of the essential oil of Rosmarinus officinalis in the control of the M. javanica (Mattei et al, 2014), the effect of the essential oil of L. alba (Verbenaceae) on hatching and mortality of juveniles of M. incognita (Gonçalves et al, 2016), the rhizome essential oil Alpinia galanga on hatching and mortality of J 2 of M. hapla (Nematoda: Tylenchida) (Jeon et al, 2016). It has been observed that the constituent compounds of the essential oils can act directly, interfering in the hatching and mortality of the nematodes in the soil (Bosenbecker, 2006), or, if they are absorbed by the plants, they may modify the composition the root exudates, interfering in the location of the roots by the nematodes, making them less attractive to the pathogen.…”
Section: Introductionmentioning
confidence: 99%